Ethiopian universal electrification development strategies - Mondal, Md. Hossain Alam; Gebremeskel, Abiti Getaneh; Gebrehiwot, Kiflom; Ringler, Claudia (International Food Policy Research Institute, 2018)
This results brief provides an overall picture of the renewable energy potential for power generation in Ethiopia and demonstrates to which extent renewable energy technologies can be integrated into the Ethiopian power sector. The results suggest that it would be attractive for the country to move forward on diversified, targeted renewable energy production, including solar PV and wind energy, to achieve universal electrification goals while also improving energy security.